Optimized sensitivity of allele-specific PCR for prenatal typing of human platelet alloantigen single nucleotide polymorphisms - P. Bugert; A. Lese; J. Meckies; W. Zieger; H. Eichler; H. Klüter (BioTechniques)
PCR using sequence-specific primers (PCR-SSP) is widely employed for the genotyping of single nucleotide polymorphisms (SNPs) in both routine diagnosis and medical research. The human platelet alloantigens (HPAs) represent SNPs in platelet-specific glycoproteins, and HPA-1, -2, -3, and -5 are the most relevant in immunohematology. In most protocols, the respective HPA-SNPs are analyzed in allele-specific reactions, each with at least 100 ng DNA. In many cases, prenatal HPA typing in the diagnosis of neonatal alloimmune thrombocytopenia is often limited by the restricted amounts of fetal DNA that are obtainable. We developed a novel PCR-SSP technique to achieve accurate HPA genotypes using only 1 ng DNA per reaction. The concentration of HPA-specific primers was increased to 1 µM each and exhibited a higher sensitivity compared to a commercial PCR-SSP kit. The modified PCR-SSP technique enabled the identification of fetal HPA genotypes using only 0.5 mL amniotic fluid (from week 16 of gestation) and from a maternal plasma sample (from week 38 of gestation). The principle of the modified PCR-SSP technique may also be applied for the genotyping of other SNPs from limited amounts of DNA.